Retention of Cardiorespiratory Anatomy Knowledge Among Universitas Ailangga Medical Students With History of COVID-19 - Akbar, Arista Widya Andhika; Sakina, Sakina; Fidiana, Fidiana; Herawati, Lilik (Universitas Airlangga, 2024)
Cardiorespiratory anatomy is fundamental knowledge for doctors. However, knowledge retention in medical students decreases over time. Retention is a reflection of memory ability and is affected by many factors, such as COVID-19 infection. COVID-19 is a disease caused by Sars-CoV-2 and has been declared as a pandemic since March 11th 2020. During the pandemic, cardiorespiratory anatomy tests were held in the 1st semester and 4th semester. The objective of this research was to measure the retention difference between students who had suffered from COVID-19 in that period and the ones without a history of COVID-19. This research was a cross-sectional descriptive analytics observational study involving 59 medical students at Universitas Airlangga, Indonesia. It was known that 19 students had suffered from COVID-19, while the other 40 had not. The average score of overall students experienced a significant decrease from 1st semester to 4th semester (p=0.000), both for students who had (p=0.023) and had not suffered from COVID-19 (p=0.001). However, the 1st semester and 4th semester cardiorespiratory anatomy scores of students with a history of COVID-19 were lower than students without a history of COVID-19. Besides scores, the cardiorespiratory anatomy knowledge retention of students who had suffered from COVID-19 (M=86.72%) was also lower than students who had not (M=86.95%). Nevertheless, the retention difference between those two groups of students was not significant (p=0.703).